GTNLARM21 / Sharifah Shafinaz Sh Abdullah ... [et al.] - Sh Abdullah, Sharifah Shafinaz; Mohamed, Zulkifli; Asmala, Aisyah Fitriah; Hanif, Nur Fatihah; Mahadi, Nur Hanisah (2021)
The name of our project is GTNLARM21. Based on the name itself, it is a combination of Glyceryl Trinitrate (GTN) medication and alarm technologies. GTN is a common medication that is used to relieve the pain from a heart attack. In this project, we used some technologies that consist of ESP32 TTGO Microcontroller, buzzer, resistor, jumper wires, breadboard, LED, HC-05 Bluetooth module, and LILYGO®TTGO T-Watch-2020 ESP32. These technologies will be set up on GTN bottles and will deliver a beep sound when it detects a spike of the heartbeat (more than 100 beats per minute) which indicates a heart attack to be happening. Patients with heart attacks must always bring their GTN medication no matter where they are going because heart attacks can happen anytime and anywhere. The main purpose why we came out with this project is to provide early prevention of heart attack as the beeping alarm will make the user or person around the user be more alert and immediately can take the medication. This action can decrease the chances of the user getting a cardiac arrest or sudden death. Therefore, the GTNLARM21 is one of the solutions that are expected to prevent this incident from happening. The cost of our project is in the range of RM350.